Multicentric and Observational Study of Omalizumab for Chronic Spontaneous Urticaria in Real-Life in Colombia - García-Gómez, Elizabeth; Chapman, Edgardo; García-Paba, María Beatriz; Ocampo-Gómez, Jaime; Egea-Bermejo, Eduardo; Garavito-De Egea, Gloria; Fang, Luis; Sarrazola, Mauricio; Sánchez-Caraballo, Jorge Mario; Serrano-Reyes, Carlos; Silva-Espinosa, Diana Lucia; Rojas-Mejía, Dolly Vanessa; et al. (Frontiers in Allergy, 2022)
Background: Although chronic urticaria (CU) is a common, cause of medical consulting both in general practitioners and allergist specialists worldwide, there is little information about its behavior and management in Latin America. Currently, national and international guidelines recommend using Omalizumab for cases refractory to management with antihistamines. Despite advances in the knowledge of Omalizumab for the management of CU, although there are few studies in underdeveloped countries, there are many studies evaluating the impact of Omalizumab treatment. There is not clinical information related with CSU-Omalizumab in patient settled in the Caribbean area. This research aims to evaluate the management of CU with Omalizumab in a real-life scenario in Colombia. Methodology: We conducted an observational, descriptive, and retrospective study with patient recruitment between 2014 - 2017 of individuals diagnosed with Chronic Urticaria (CU) treating allergology specialists in five Colombian cities. We included patients with CU who failed to achieve disease control after treatment for four weeks with fourfold doses of second-generation H1-antihistamines, as recommended by the EAACI/GA²LEN/EDF/WAO guidelines and who received treatment with Omalizumab. Results: We included 123 patients, 73.1% (n= 90) were women. The mean age was 47.1 years (Standard Deviation, SD: 16.2). The median of the total months of disease evolution was 30 (IQR= 13 - 58). 81.3 % (n= 100) of patients were diagnosed with chronic spontaneous urticaria – CSU. 4.8% (n= 6) had inducible CU (CIndU), and 13.8% (n= 17) reported mixed urticaria (spontaneous CU with at least one inducible component). Regarding emotional factors, 34.9% (n= 43) of subjects indicated anxiety symptoms, 34.1% (n= 42) had exacerbations associated with stress, and 14.6% (n= 18) manifested episodes of sadness. The percentage of patients with CSU controlled according to medical criteria at three months with Omalizumab were 80% (n= 80/100) and at six months 87% (n= 87/100). The frequency of adverse events was 29.2% (n= 36), with headache being the most frequent adverse event. Conclusions: This real-life study with Omalizumab at CU describes percentages of effectiveness and safety similar to those observed in pivotal and real-life studies conducted in other regions around the world.